The Relationship between Ownership Structure Dimensions and Corporate Performance: Evidence from Bahrain - Reem Khamis; Allam Mohammed Hamdan; Wajeeh Elali (Australasian Accounting, Business and Finance Journal, 2015)
In this study we examine the relation between ownership structure and corporate performance; the sample of the study included 42 out of 48 companies of all sectors in Bahrain Bourse in five years from 2007-2011. Several dimensions of ownership concentration were studied in addition to managerial and institutional ownership. Two different measurements of performance were used (ROA and Tobin’s Q). The study investigated this relation using several control variables and 2SLS statistical method to overcome the problem of endogeneity that may exist between the study variables. It was found that ownership concentration have a negative effect with statistical significance on company performance. Institutional ownership was found to have a positive effect on company performance. Managerial ownership was not found to have a significant effect on company performance, however it was found that managerial ownership has a positive effect on performance only in the case of declining ownership concentration. Other results were revealed by the study regarding company age, size, growth, board size and liquidity. The study is considered to have theoretical and practical implications. It contributes to the debate about agency theory and managerial entrenchment. It also may help officials in Bahrain in making laws and legislations concerning corporate governance improvement in Bahraini market.